Programa educativo del balonmano en el desarrollo de su rendimiento físico en estudiantes del sexto grado de primaria en la Institución Educativa Primaria Secundaria de Menores N°60756 Claverito, Iquitos 2022 - Ramirez Quevedo, Anthony Edward (2025)
The present research aims to implement a handball educational program aimed at promoting the physical productivity of sixth grade primary school students at School No. 60756 "Claverito", located in Iquitos during the year 2022. This study is framed within an explanatory design and uses a quasi-experimental approach, focusing solely on an experimental group to evaluate their progress in physical performance. The target population consisted of sixth grade students from the aforementioned educational institution. We worked with an experimental group (group B) made up of 30 students and a control group (group C) also with 30 students. For data collection, physical fitness tests were applied, the validity of which was confirmed through expert judgment, reaching a reliability of 84%. After analyzing the data, it was inferred that the handball training plan had a beneficial impact on physical performance in sixth grade students, thus accepting the hypothesis raised in the study.